Meta-analysis of hybrid immunity to mitigate the risk of Omicron variant reinfection - Huiling Zheng; Huiling Zheng; Shenggen Wu; Wu Chen; Shaojian Cai; Meirong Zhan; Cailin Chen; Jiawei Lin; Zhonghang Xie; Jianming Ou; Wenjing Ye (Frontiers Media S.A., 2024)
BackgroundHybrid immunity (a combination of natural and vaccine-induced immunity) provides additional immune protection against the coronavirus disease 2019 (COVID-19) reinfection. Today, people are commonly infected and vaccinated; hence, hybrid immunity is the norm. However, the mitigation of the risk of Omicron variant reinfection by hybrid immunity and the durability of its protection remain uncertain. This meta-analysis aims to explore hybrid immunity to mitigate the risk of Omicron variant reinfection and its protective durability to provide a new evidence-based basis for the development and optimization of immunization strategies and improve the public's awareness and participation in COVID-19 vaccination, especially in vulnerable and at-risk populations.MethodsEmbase, PubMed, Web of Science, Chinese National Knowledge Infrastructure, and Wanfang databases were searched for publicly available literature up to 10 June 2024. Two researchers independently completed the data extraction and risk of bias assessment and cross-checked each other. The Newcastle-Ottawa Scale assessed the risk of bias in included cohort and case-control studies, while criteria recommended by the Agency for Health Care Research and Quality (AHRQ) evaluated cross-sectional studies. The extracted data were synthesized in an Excel spreadsheet according to the predefined items to be collected. The outcome was Omicron variant reinfection, reported as an Odds Ratio (OR) with its 95% confidence interval (CI) and Protective Effectiveness (PE) with 95% CI. The data were pooled using a random- or fixed-effects model based on the I2 test. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed.ResultsThirty-three articles were included. Compared with the natural immunity group, the hybrid immunity (booster vaccination) group had the highest level of mitigation in the risk of reinfection (OR = 0.43, 95% CI:0.34-0.56), followed by the complete vaccination group (OR = 0.58, 95% CI:0.45-0.74), and lastly the incomplete vaccination group (OR = 0.64, 95% CI:0.44-0.93). Compared with the complete vaccination-only group, the hybrid immunity (complete vaccination) group mitigated the risk of reinfection by 65% (OR = 0.35, 95% CI:0.27-0.46), and the hybrid immunity (booster vaccination) group mitigated the risk of reinfection by an additional 29% (OR = 0.71, 95% CI:0.61-0.84) compared with the hybrid immunity (complete vaccination) group. The effectiveness of hybrid immunity (incomplete vaccination) in mitigating the risk of reinfection was 37.88% (95% CI, 28.88-46.89%) within 270-364 days, and decreased to 33.23%% (95% CI, 23.80-42.66%) within 365-639 days; whereas, the effectiveness after complete vaccination was 54.36% (95% CI, 50.82-57.90%) within 270-364 days, and the effectiveness of booster vaccination was 73.49% (95% CI, 68.95-78.04%) within 90-119 days.ConclusionHybrid immunity was significantly more protective than natural or vaccination-induced immunity, and booster doses were associated with enhanced protection against Omicron. Although its protective effects waned over time, vaccination remains a crucial measure for controlling COVID-19.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier, CRD42024539682.